A religiosidade como mediadora dos processos de territorialização dos sujeitos de Boa Vista em Goiás (1840 – 1940): Religiosity as mediator of territorialization processes of Boa Vista do Tocantins subjetcs in Goiás (1840 – 1940) (Revista de História da UEG (REVHIST), 2021)
The following article aims to present to what extent the culture of religiosity mediated the territorialization processes of Boa Vista do Tocantins sertanejos and political leaders - GO. Given that issue, bibliographic and documental inquiry methodology was used, seeking to weave a hermeneutical analysis from an interdisciplinary perspective. It is noticed that religiosity became a mediator of strong influence in the territorialization of subject’s processes of Boa Vista do Tocantins. The agents that took part in the religious area and acted as such charismatic leaders operated in an arbitrary manner considering their own interests to domination, not only of the religious field but also the politics, economic and cultural ones.Keywords: Religiosity. Boa Vista do Tocantins. Territorialization. Culture.